Perlakuan Pematangan Buatan pada Pepaya (Carica papaya L.) Varietas IPB 9 untuk Perbaikan Sistem Distribusi - Emmy Darmawati; Ken Sutrisno; Mohammad Iqwal Tawakal (Jurnal Ilmu Pertanian Indonesia, 2018)
Papayas as a climacteric fruit are commontly harvested and distributed in an unripe state with various of maturities. Ripening is required before papaya ready for consumption. The objectives of this research were to analyze the response of artificial ripening treatment for papaya in order to perform the best marketing schedule. This study was started by harvesting, sorting, cleaning, hot water treatment, and transportation simulation similar to 90.44 km, storage in refrigerator at 15 °C, artificial ripening treatment and storage at room temperature. Physical quality parameters measured consisted of weight loss, color, firmness, and total soluble solid. Artifial ripening using ethephon will accelerate the maturation of papaya. Papaya with maturity level of 60% (yellow tinge) that stored at 15 °C for 7 days was found still not ready to be consumed as a table fruit, and it was still necessary to artificially ripening process. Artificial ripening using ethephon of 250 and 750 ppm did not significantly affect the fruit color, hardness, and total soluble solids. This papaya could be consumed after 2 days of ripening and reached the optimum conditions for consumption after 4 days, with a possibility of shelf life for 6 days at room temperature. The best artificial ripening treatment for papaya that had been stored 14 days at 15 °C was by using 250 ppm of ethephon. The use of 250 ppm ethephon would make the best visually and smoothly yellow color of papaya’s peel surface.